Sing with Your Baby Book & CD set - Galvin, Laura Gates; Giblin, Brain E; Heather, Lucas; Rabe, Tish (New York Studio Mouse, 2006)
Your baby loves to hear you read...and sing! Filled with eye-catching photos of families both furry and human, this interactive book and CD includes tips to help parents and babies enjoy discovering the world together. Sing-along songs include traditional favorites and brand-new tunes
Rhyms & songs
Sesame Beginners
2 13 14
Keywords: English poetry